Divine Custody : A History of Singapore's Oldest Teochew Temple - Yeo, Kang Shua, 1975- (Book collections on Project MUSE., 2021)
Teochew-speaking gambier and pepper farmers were early settlers of Singapore at the turn of the 19th century. Wak Hai Cheng Bio, now surrounded by the skyscrapers of Singapore's central business district, traces its history back to the earliest days of the colony. Its two deities - the Emperor of Heaven and Mazu, the Goddess of the Seas, tutelary deities of the Teochew people and travellers by sea respectively, long accompanied the sojourns of Teochew-speakers in the region. No written sources or inscriptions commemorate the founding of the temple, but the author's research in the history of l.